Wanderungsmuster junger Frauen im ländlichen Sachsen-Anhalt – Implikationen für zielgruppenorientierte Regionalentwicklungsstrategien - Wiest, Karin; Leibert, Tim (Raumforschung und Raumordnung | Spatial Research and Planning, 2013)
In many regions of Europe pronounced disparities between the proportions of women and men in younger age groups can be observed. While cities tend to display a surplus of young women, sparsely populated rural areas are often characterised by a surplus of young men. Rural areas in the new federal states (former East Germany) are especially affected by a striking “lack” of women. This paper analyses the causes of this demographic imbalance using the example of Saxony-Anhalt and investigates its implications for regional development. In-depth interviews with young women, a questionnaire for school pupils both male and female, and the analysis of demographic data provide a basis for demonstrating how a specific path of demographic development has been generated by the crisis of social and economic transformation that followed reunification, the regional economic structure and the emergence of a culture of migration in rural Saxony-Anhalt. The primary factors that explain the migration of young women are long ongoing difficulties on the labour market, negatively perceived career opportunities, and a low level of identification with the region of origin. The findings of the investigation show that the analysis of the phenomenon of unbalanced gender proportions not only draws attention to gender-specific realms but also always touches upon the question of equivalent living conditions and spatial discourses.
Keywords: Gender; Migration; Rural areas; Regional development; Culture of out-migration; Saxony-Anhalt